Pemberdayaan Ibu dan Pemberian Mitekor Padat Gizi untuk Meningkatkan Status Gizi Anak Sekolah di Deli Serdang: Pemberdayaan Ibu dan Pemberian Mitekor Padat Gizi untuk Meningkatkan Status Gizi Anak Sekolah di Deli Serdang - Riris Oppusunggu; Mahdiah; Ratna Zahara; Adriana Hamsar (Amerta Nutrition, 2026)
Background: Stunting is a serious public health challenge that affects child growth and development. Objectives: This study evaluated the impact of nutrient-dense mitekor and maternal nutrition education on the nutritional status of stunted school-aged children in Deli Serdang, Indonesia. Methods: Using a quasi-experimental design, 30 children aged 6-8 years received 100 g of mitekor daily for 30 days, while their mothers participated in weekly education sessions. Nutritional intake, anthropometric measurements, and maternal knowledge were assessed before and after the intervention. Results: The results showed significant increases in children's intake of protein (+6.86 g), carbohydrate (+9.6 g), calcium (+319.27 mg), and zinc (+0.87 mg). The proportion of children with normal height-for-age scores increased from 6.7% to 36.7%, indicating a positive impact on growth. Maternal knowledge scores also improved significantly, indicating the effectiveness of the educational intervention. Conclusions: This study underscores the importance of integrating local food-based solutions with caregiver empowerment in addressing the problem of stunting. The findings suggest that such interventions are feasible and impactful in resource-limited settings. Future research should explore long-term outcomes and the potential to expand this intervention to a wider population.